Determinants of Caregivers' Use and Adoption of Household Water Chlorination: A Qualitative Study with Peri-urban Communities in the Peruvian Amazon - Rothstein, Jessica D. (Am J Trop Med Hyg, 2015)
The gap between the efficacy and the effectiveness of household water treatment in reducing diarrhea-related morbidity indicates the need for a better understanding of the determinants of long-term behavior change. To explore the barriers to drinking water chlorination in the Peruvian Amazon, where diarrhea is endemic among under-5 children, we conducted qualitative research with 23 caregivers from peri-urban communities of Iquitos, Peru. Our inquiry drew on the Transtheoretical Model of behavior change and the Integrated Behavioral Model for Water, Sanitation, and Hygiene to identify the most relevant contextual, psychosocial, and technological determinants of initial action and long-term adoption of chlorination. Our findings suggest that the decision to try out this practice resulted from the combined effect of knowledge of chlorination benefits and product availability and affordability. Progress from action to adoption was influenced by caretakers' understanding of dosage, the packaging of chlorine products, knowledge and skills for multipurpose laundry bleach, the taste of treated water, and reinforcement. This analysis suggests that a focus on these determinants and the household domain may help to improve the sustainability of future intervention efforts.